How do people who use opioids express their qualities and capacities? An assessment of attitudes, behaviors, and opportunities - Jerel M. Ezell; Mai T. Pho; Elinor Simek; Babatunde P. Ajayi; Netra Shetty; Suzan M. Walters (Harm Reduction Journal, 2024)
Abstract People who nonmedically use drugs (PWUD) face intricate social issues that suppress self-actualization, communal integration, and overall health and wellness. “Strengths-based” approaches, an under-used pedagogy and practice in addiction medicine, underscore the significance of identifying and recognizing the inherent and acquired skills, attributes, and capacities of PWUD. A strengths-based approach engenders client affirmation and improves their capacity to reduce drug use-related harms by leveraging existing capabilities. Exploring this paradigm, we conducted and analyzed interviews with 46 PWUD who were clients at syringe services programs in New York City and rural southern Illinois, two areas with elevated rates of opioid-related morbidity and mortality, to assess respondents’ perceived strengths. We located two primary thematic modalities in which strengths-based ethos is expressed: individuals (1) being and advocate and resource for harm reduction knowledge and practices and (2) engaging in acts of continuous self-actualization. These dynamics demonstrate PWUD strengths populating and manifesting in complex ways that both affirm and challenge humanist and biomedical notions of individual agency, as PWUD refract enacted, anticipated, and perceived stigmas. In conclusion, programs that blend evidence-based, systems-level interventions on drug use stigma and disenfranchisement with meso and micro-level strengths-based interventions that affirm and leverage personal identity, decision-making capacity, and endemic knowledge may help disrupt health promotion cleavages among PWUD.